EFFICACY OF DRUG-FREE THERAPY OF HYPERTENSION DISEASES IN THE EARLY STAGE OF THE DISEASE - Khusainova Munira Alisherovna; Yarmatov Suvon Totlibayevich; Gafforov Xudoyor Xudoyberdiyevich; Kamolova Diyora Jamshedovna (Journals Park Publishing, 2022)
Hypertension is a disease whose leading symptom is an increase in blood pressure. This disease is widespread and occurs equally often in both men and women, more often after 40 years. Blood pressure is measured in millimeters of mercury (mmHg) and has two numbers. The first means systolic pressure, the second - diastolic. According to the definition of the World Health Organization, a person has high blood pressure or hypertension when the first pressure exceeds 140 mmHg and / or the second exceeds 90 mmHg. It should be borne in mind that the criteria for increased blood pressure are largely conditional, since between the level of blood pressure and the risk of cardiovascular diseases (CVD) there is a direct relationship, starting with a value of 115/75 mmHg.
Keywords: hypertension, acupuncture, hirudotherapy, body reflexotherapy